Teori Feminis tentang Identitas dan Subjektivitas - Kusumastuti, Nunik; Putra, Gilang Rizki Aji (BULETIN ADALAH, 2024)
This article reviews the contribution of feminist theory to the understanding of individual identity and subjectivity. Feminist theory highlights that a person's identity and subjective experiences are not neutral or isolated, but are deeply influenced by social and gender position in society. This approach broadens our view of subjectivity by recognizing the diversity of individual experiences based on factors such as gender, social class, race, and sexuality. This article also examines feminist criticism of universalism in identity theory, as well as how feminism invites to see individuals as complex subjects within existing power dynamics and social structures.